THE USE OF DIGITAL TECHNOLOGIES IN THE TRAINING OF SOCIONOMIC SPECIALTIES FOR WORK IN INCLUSIVE EDUCATIONAL CONDITIONS - V. Berezan; N. Pakhomova; V. Pakhomova (Естетика і етика педагогічної дії)
The article considers and analyzes the problem of using digital technologies in the preparation of specialists in socionomic specialties to work in an inclusive educational environment. The essences of inclusive education, the regulatory framework of inclusive education in Ukraine, and socio-pedagogical and correctional work with children with special educational needs are revealed. The role of a social pedagogue, speech pathologist, and speech therapist in working with children with special educational needs in inclusive education is determined. The article considers the possibilities of using digital technologies in the work of specialists in socionomic specialties in the context of inclusive education and ways to improve the system of their training.